Evaluation of Gunshot Detection Algorithms - Chacon Rodriguez, Alfonso (2011)
Six preprocessing algorithms for the detection of firearm gunshots are statistically evaluated, using the receiver operating characteristic method as a previous feasibility metric for their implementation on a low-power VLSI circuit. Circuits are intended to serve as the input detection sensors of a low-power environmental surveillance network. Some possible VLSI implementations for the evaluated algorithms are also evaluated. Results indicate that the use of wavelet bank filters, either discrete or continuous, might be the best choice in terms of the compromise between detection efficiency and the power requirements of the intended application